Enterobacteriaceae isolates: Clinical, Bacterial and Antimicrobial Profile in a Tertiary Teaching Hospital - K. Pawar, Satyajeet; T.Mohite, S.; Kakade, S.V.; Karande, G.S. (International Journal of Psychosocial Rehabilitation, 2020)
Members of Enterobacteriaceae family are the leading pathogens among Gram negative bacteria which are associated with critical infection of community or hospital origin. These Enterobacteriaceae members are considered critical as they are associated with drug resistance mechanism which includes synthesis of enzymes like β-lactamase, extended spectrum β-lacatamse, AmpC and carbapenemase.This results into inadequate antimicrobial therapy, increased hospitalization, and cost to patient with increased mortality and morbidity. To find out clinical, bacterial and antimicrobial profile of Enterobacteriaceae clinical isolates from a tertiary teaching center. Total 2002 clinical strains belonging to Enterobacteriaceae family, isolated, from June 2016 to April 2018, were included for study purpose. Identification of bacteria was done by VITEK 2 compact (Biomerieux) automation system, and antimicrobial susceptibility testing was done with the same system to detect minimum inhibitory concentrations for different group of antimicrobials.CLSI 2016 guidelines were used for interpretations of results. Urine (39.4 %, n = 788) and pus 486 (24.3%) were two leading specimens which isolated Enterobacteriaceae isolates. Total 917 Escherichia coli (45.8%) were isolated followed by 839 (41.9 %) Klebsiella spp. Of the least isolated were Salmonella spp. and Shigella spp. Ampicillin showed sensitivity rate of 25.3 % while for cephalosporins it was between 20.2 to 33.9 %.Tigecyclin and colistin had comparatively higher sensitivity of 76.9 % and 74.6 %. Amikacin from the aminoglycosides had 73.2 % of sensitivity. Carbapenems showed a sensitivity range of 45.8 to 58.9 %. Antimicrobials like cephalosporins, penicllins, aminoglycosides, and quinolones are of little use because of increased resistance patterns .The most effective antimicrobials were amikacin, colistin.and tigecyclin.